(untitled) (Historia, 2021)
It is the purpose of this study to ascertain what the nature and extent of the British and Boer strategic planning (if any) before the outbreak of the Anglo-Boer War was, to indicate how they implemented their strategies, and to show what the implications of their strategies were for both the military course of events during the war as well as for the civilian population (of all races) in the war zone. To start off with, the terms strategy and tactics are explained and compared, and a review is given of the principles of strategy. Thereafter the British preparations for a war in what is today South Africa, are discussed, and it is concluded that when the war broke out on 11 October 1899, Britain was not ready to take on the two small Boer republics. However, the Boers also neglected to plan properly for war, and consequently they squandered their only chances to defeat the British Army in South Africa to such an extent that the British government might have been forced to negotiate a peace treaty that would have guaranted Boer independence. A review is given of the military-strategic course of events during the war, and it is clear that the war was one of missed strategic opportunities for both the British and the Boers. Eventually the British Army blundered its way to a contentious victory, leaving behind a trail of destruction and bitterness.